Potential Factors to Enhance the Level of Disclosure within Financial Statements of Indonesian Provincial Governments - Johan Arifin (Institute of Research and Community Outreach - Petra Christian University, 2019)
Using Agency theory, this research aims to examine the factors that potentially influence the level of disclosure within financial statements in Indonesian provincial governments including Human Development Index (HDI), Liabilities, General Allocated Fund (GAF), and Provincial Original Revenue (POR). This research is very important because Indonesia has recently undergone major governmental financial reform and is seeking to greatly enforce its financial accounting transparency. The objects of this research are 99 financial statements from 33 Indonesian provinces in the period of 2014 to 2016. The level of disclosure is measured using a 34 item index derived from Indonesian Government Accounting Standards. Regression analysis shows that Human Development Index (HDI) and General Allocated Fund (GAF) are positive and significant predictors of the level of disclosure within financial statements of Indonesian provincial govern- ments. These results can be used by Indonesian government as a potential information in making government policy related to financial transparency at provincial level.